ChemInform Abstract: Transition Metal‐Mediated Direct C—H Arylation of Heteroarenes Involving Aryl Radicals. Issue 22 (3rd June 2014) - Bonin, Helene; Sauthier, Mathieu; Felpin, Francois‐Xavier
Abstract Review: [96 refs.